"If I'm shinin', everybody gonna shine": centering Black fat women and femmes within body and fat positivity. Issue 3 (2nd September 2021) - Senyonga, Mary; Luna, Caleb
ABSTRACT: In this article, we negotiate the tension of Lizzo's embodiment and the work she is forced to perform to appease and mollify both thin and non-Black audiences. As a Black fat rapper, singer, dancer, and performer, Lizzo at once disrupts the normative image of a performer and becomes a commodified representation of body positivity. Her self-love messaging undoubtedly touches a broad fan base who look to her for guidance and inspiration. But how is she taken up by audiences dissimilar to her? Lizzo's body-positive politic is presented as being particularly interested in disrupting body terrorism, while some audiences perceive it as a neoliberal model of self-love, failing to challenge systems. We consider ways in which Black fat bodies are consumed and used for their utility, while broader relationships to other Black fat people remain unchanged. We map selections from Lizzo's creative output in 2019 to demonstrate racialization and fat embodiment intertwined in her performances, leading to the necessary coalition that fat activism must adopt.